PENDAMPINGAN PROMOSI KRUPUK AMPLANG MELALUI MEDIA SOSIAL SEBAGAI UPAYA PENINGKATAN PENJUALAN DI DESA KERTASADA KEC. KALIANGET - Purwati Ratna Wahyuni; Hopid (Kreativitas Pada Pengabdian Masyarakat (Krepa), 2024)
Service is one of the tridharma that must be carried out by lecturers. This briefing was given to managers of Small and Medium Enterprises (MSMEs) Amplang Cracker in Kertasada Village, Kalianget District, Sumenep Regency which aims to develop strategies for increasing sales and developing the business so that it continues to grow in the future. MSME players have changed their marketing orientation due to the pandemic, many MSME players have turned to electronic commerce (e-commerce) to increase sales but this is not supported by the ability of MSME players who tend to be low in using technology. This service aims to provide understanding and skills for MSMEs in Kertasada Village, Kalianget District, Sumenep Regency about the use of social media as a means of effective and efficient product sales/promotion and provide assistance in utilizing various internet-based market places as a means of selling product results. This activity uses a contextual approach method, namely providing theoretical material first and continued with a workshop directly uploading products produced by MSME actors in Kertasada Village. The result of this service activity is an increase in sales of Dumpling Cracker products processed by MSMEs in Baban Village, Gapura District, Sumenep Regency.